Pemetaan Informasi Banjir Beberapa Titik Di Palembang Berbasis Internet of Thing - Eleonora Arthi Dwi Yovita; Klaudius Jevanda BS (CV. ITTC INDONESIA, 2026)
The purpose of this research is to develop an Internet of Things (IoT)-based flood monitoring and early warning system for several locations in Palembang, which is displayed visually using a Geographic Information System (GIS). The system was developed using the Waterfall method, starting from the requirements analysis, design, implementation, testing, deployment, and maintenance. Water level measurements are taken using HC-SR04 ultrasonic sensors controlled by NodeMCU ESP8266. The information is sent in real time to the Blynk application and sends warning notifications via Telegram according to the specified threshold with a status of risky or safe route. Test results show that the system is capable of displaying real-time water level readings on Blynk and sending Telegram notifications with a delay of approximately 1.0–1.2 seconds. The ultrasonic sensor shows a small measurement difference compared to manual measurements, and the Neo-6M GPS module displays location coordinates with a difference of approximately 1–2 meters. These results indicate that the system can be used to support the monitoring of flood-prone areas and increase community preparedness.